Four new species of Mesoamerican biting midges of the genus Culicoides (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2015)
Four new species of biting midges, Culicoides (Culicoides) fortinensis sp. nov. from Mexico (Veracruz), Culicoides (Culicoides) rulfoi sp. nov. from Mexico (Michoacan), Costa Rica and Panama, Culicoides (Anilomyia) pseudodecor sp. nov. from Mexico (Morelos and Veracruz) and Culicoides woodruffi sp. nov. from Mexico (Morelos), are described and illustrated based on adults. The new species are compared with their most similar congeners. The species are all distributed at higher elevations.